Comparative Effects of Monday–Thursday and Daud Fasting Regimens on Serum Testosterone Levels in Male Wistar Rats (Rattus norvegicus) - Nanda Fadhilah Witris Salamy; Wiwik Winarningsih; Nur Intania Puteri Kusnandar; Zamirah Mabarroh El Haque (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Intermittent fasting has attracted increasing attention because of its metabolic and endocrine benefits. However, evidence regarding the effects of non-daily fasting regimens, particularly Monday–Thursday fasting and Daud fasting, on male reproductive hormones remains limited. This study compared the effects of these regimens on serum testosterone levels in male Wistar rats. Methods. A true experimental study with a post-test-only control group design was conducted using 27 healthy male Wistar rats (Rattus norvegicus). Animals were randomly assigned to a control group, a Monday–Thursday fasting group, or a Daud fasting group (n = 9/group). The fasting groups underwent 12-hour daily feeding restriction (18:00–06:00) for 21 days, comprising six and ten fasting days, respectively. Serum testosterone levels were measured using ELISA and analyzed by one-way ANOVA followed by Tukey's post hoc test. Results. Mean serum testosterone concentrations were 15.003 ± 3.55 mg/dL in the control group, 11.682 ± 3.05 mg/dL in the Monday–Thursday fasting group, and 8.501 ± 1.31 mg/dL in the Daud fasting group. Significant differences were observed among groups (p < 0.001). Both fasting groups showed significantly lower testosterone levels than the control group (p = 0.049 and p < 0.001), whereas no significant difference was found between the two fasting regimens (p = 0.061). Conclusion. Both Monday–Thursday fasting and Daud fasting for 21 days were associated with reduced serum testosterone levels in male Wistar rats. Further studies should control energy intake and evaluate hormonal and metabolic biomarkers to clarify the underlying mechanisms.